PERSONALITY TRAITS AND ENTREPRENEURIAL INTENTIONS OF BUSINESS ADMINISTRATION STUDENTS OF SELECTED HIGHER EDUCATION INSTITUTIONS IN PAMPANGA, PHILIPPINES - Mendoza, Darriel B.; Lacap, Jean Paolo (PEOPLE: International Journal of Social Sciences, 2015)
The study aims to identify the personality traits of the business administration students and how these traits affect their entrepreneurial intentions. Specifically, the undertaking tries to examine the (1) significant relationships between the respondents’ personality traits and their entrepreneurial intentions; (2) significant difference between the respondents’ sex and their personality traits; and (3) significant difference between the respondents’ sex and their entrepreneurial intentions. The respondents were randomly selected in the five higher education institutions in Pampanga, Philippines. Using correlational-descriptive research, the undertaking revealed that the respondents’ openness to experience, conscientiousness, agreeableness, and neuroticism have significant relationship to entrepreneurial intentions. On one hand, respondents’ extraversion reflects no significant relationship to entrepreneurial intentions. Overall, there is statistically significant relationship between respondents’ personality traits and their entrepreneurial intentions. Furthermore, there is statistically significant difference between the respondents’ sex and openness to experience, conscientiousness, and extraversion. Contrary, no significant difference was observed between the respondents’ sex and agreeableness and neuroticism. In totality, there is a statistical significant difference between the respondents’ sex and their entrepreneurial intentions.